Customized ping tool for smart grid communication network testing - Quang D.N.; See O.H.; Nga D.V.; Chee L.L.; Xuen C.Y.; Karuppiah S.A.L.; Fadzil M. (IEEE Computer Society, 2023)
Heterogeneous and hybrid smart grid communication network is a network that comprises of different communication mediums and technologies. Performance evaluation is one of the main concerns in smart grid communication system. In any smart grid communication implementation, to determine the performance factor of the network, a testing of an end-to-end process flow is required. Therefore, an effective testing tool plays a crucial role in evaluating the performance of smart grid communications. Ping is currently one of the most widely used tools. In this paper, a customized ping utility, called Smart Grid Ping, is introduced. This utility provides random ping intervals with user selectable distribution, allowing network administrators to test the reachability and availability of various applications in smart grid communication system. 2012 IEEE.